A Study of Islamic Worldview Follows an Education System: Reveals the Spiritual Tendencies of Adolescents - Nuriman Nuriman; Yuliza Yuliza; Yusnaini Yusnaini (DAYAH: Journal of Islamic Education, 2023)
The main goal of the study was to identify adolescents' worldviews following Traditional Education, Boarding Schools, and Senior High School types. The variables were examined with One-way ANOVA and T-Test analysis to identify the aspects of worldly and spiritual which involved 390 in the age range of 16-21 years and consisted of 150 males and 240 females of adolescents. The systematic random sampling and questionnaire version of the MRPI were employed for the data collection procedure. The worldly aspect is found insignificantly and the spiritual significantly differs following educational types.  It was the basis of forming the adolescents' spirituals of diversity.